Abatacept with methotrexate versus other biologic agents in treatment of patients with active rheumatoid arthritis despite methotrexate: a network meta-analysis. - Guyot, P; Taylor, P; Christensen, R; Pericleous, L; Poncet, C; Lebmeier, M; Drost, P; Bergman, G (BioMed Central, 2011)
INTRODUCTION: The goal of this study was to compare the efficacy in terms of Health Assessment Questionnaire change from baseline (HAQ CFB), 50% improvement in American College of Rheumatology criterion (ACR-50) and Disease Activity Score in 28 joints (DAS28) defined remission (< 2.6) between abatacept and other biologic disease modifying anti-rheumatic drugs (DMARDs) in patients with rheumatoid arthritis (RA) who have inadequate response to methotrexate (MTX-IR). METHODS: A systematic literature review identified controlled trials investigating the efficacy of abatacept (three studies), etanercept (two studies), infliximab (two), adalimumab (two), certolizumab pegol (two) ritixumab (three), and tocilizumab (two) in MTX-IR patients with RA. The clinical trials included in this analysis were similar with respect to trial design, baseline patient characteristics and background therapy (MTX). The key clinical endpoints of interest were HAQ CFB, ACR-50 and DAS28 < 2.6 measured at 24 and 52 weeks. The results were analysed using network meta-analysis methods that enabled calculation of an estimate for expected relative effect of comparative treatments. Analysis results were expressed as the difference in HAQ CFB score and odds ratio (OR) of achieving an ACR-50 and DAS28 response and associated 95% credible intervals (CrI). RESULTS: The analysis of HAQ CFB at 24 weeks and 52 weeks showed that abatacept in combination with MTX is expected to be more efficacious than MTX monotherapy and is expected to show a comparable efficacy relative to other biologic DMARDs in combination with MTX. Further, abatacept showed comparable ACR-50 and DAS28 < 2.6 response rates with other biologic DMARDs at 24 and 52 weeks, except for ACR-50 compared to certolizumab pegol at 52 weeks and for DAS28 < 2.6 compared to tocilizumab at 24 weeks. Sensitivity analyses confirmed the robustness of the findings. CONCLUSIONS: Abatacept in combination with MTX is expected to result in a comparable change from baseline in HAQ score and comparable ACR-50 and DAS28 < 2.6 response rates in MTX-IR patients compared to other approved biologic agents.